A method for stress relief by positive pressure annealing of zinc sulfide
Patent Information
- Application Number
- CN202610839969.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-11
- Publication Date
- 2026-09-01
AI Technical Summary
存在能耗高、效果一般等缺点,无法满足高效规模化量产需求
[0023] The beneficial effects of adopting the above-mentioned further technical solution are as follows: When the temperature drops to 125℃, argon gas continues to be circulated and pressure is controlled, the heating system is shut off, the first insulation layer inside the furnace is opened, allowing the gas inside the cavity to circulate fully and the temperature to be fully released. The temperature drops rapidly to room temperature along with the furnace. The process design of uniformly cooling down to 120-130℃ in 50-70 hours avoids stress rebound caused by rapid cooling and accurately matches the critical temperature of zinc sulfide lattice diffusion. Below 125℃, lattice diffusion basically stops, and no new thermal stress is generated. There is no risk of stress rebound. While ensuring the stress relief effect, the ineffective cooling time is greatly shortened, and the total process cycle is precisely controlled to about 5 days.
Smart Images

Figure CN122669490A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of heat treatment technology for infrared optical crystal materials, and specifically relates to a method for stress relief by positive pressure annealing of zinc sulfide. Background Technology
[0002] Currently, the annealing stress relief process for multispectral zinc sulfide mainly includes two types: atmospheric pressure annealing and negative pressure annealing, with negative pressure annealing including vacuum annealing. The process involves atmospheric pressure annealing, followed by heating, cooling, and heating again. After several cycles, the temperature is slowly reduced to room temperature, with a total process cycle exceeding 10 days. In addition, for large-sized and thick products, the processing cycle will be extended further. Ultimately, the residual stress of the workpiece can be reduced to about 20 nm / cm. Such short-time processing is only suitable for workpieces of conventional size, and the processing effect is generally not good for products with large thickness and large diameter. Using negative pressure annealing, after heat preservation and cooling, the total process cycle is more than 15 days, which can reduce residual stress to below 35nm / cm, but there are problems of high-temperature decomposition and performance damage of the workpiece. To achieve full stress release, existing processes typically require a total holding time of ≥150 hours and a total cooling time of ≥100 hours, with a total process cycle ranging from a minimum of 10 days to a maximum of 20 days or even longer. These processes suffer from drawbacks such as high energy consumption and mediocre performance, failing to meet the demands of efficient, large-scale mass production.
[0003] For large-size, thick, multispectral zinc sulfide, heat conduction is mainly radiation under normal and negative pressure environments. The temperature difference between the core and surface of the workpiece is large, which easily leads to large stress gradients and excessive local stress, especially at the product edges. Existing processes cannot balance efficiency and uniform stress relief.
[0004] Negative pressure environments exacerbate the high-temperature sublimation and decomposition of ZnS, generating defects such as sulfur vacancies and reducing optical transmittance and uniformity. The ultra-long-term high-temperature insulation used to achieve stress relief can easily lead to abnormal grain growth, resulting in a decrease in the mechanical properties of the material, such as bending strength and fracture toughness, which cannot meet the reliability requirements of high-end equipment.
[0005] Existing processes can only improve stress relief by extending the heat preservation time. Even with heat preservation exceeding 100 hours, the residual stress of conventional products can only be stably controlled below 35 nm / cm, and it is impossible to achieve a low stress level below 20 nm / cm in a short period of time. Summary of the Invention
[0006] This invention designs a method for stress relief by positive pressure annealing of zinc sulfide, comprising the following steps: S1: workpiece pretreatment: covering the outside of the zinc sulfide workpiece with graphite fiber and placing the zinc sulfide workpiece into the furnace; S2: Pretreatment of gas inside the furnace: After sealing the furnace, vacuum the furnace, then fill the furnace with protective gas and exhaust the gas to atmospheric pressure. S3: Establish positive pressure atmosphere: After the furnace is at normal pressure, continue to fill the furnace with protective gas and exhaust it to positive pressure; S4: Heat treatment: Heat the furnace, and then keep it warm. During the heat treatment, keep the furnace filled with protective gas and exhaust gas to maintain positive pressure. S5: Annealing treatment: After heating to the first annealing temperature, hold the temperature, then cool down. After reaching the second annealing temperature, stop heating and let it cool to room temperature. During the annealing treatment, keep the furnace filled with protective gas and exhaust gas to maintain positive pressure.
[0007] Compared with existing technologies, the beneficial effects of this invention are as follows: By using graphite fiber wrapping and positive pressure temperature uniformity design, the temperature and stress gradients between the material's interior and surface are eliminated, allowing stress to be transmitted slowly and avoiding excessive deformation of the workpiece and changes in surface precision; by establishing a positive pressure atmosphere, the atomic diffusion ability of zinc sulfide is enhanced, which can inhibit the sublimation and decomposition of zinc sulfide, optimize the heat preservation time, avoid abnormal grain growth caused by prolonged high temperature, and ensure that the optical transmittance, uniformity, and mechanical properties of multispectral zinc sulfide are not reduced after treatment; at high temperature, the stress is evenly distributed in various parts of the interior and released evenly and slowly to the outside. When eliminating stress, it is coordinated with parameters such as positive pressure, temperature, atmosphere, and heating and cooling rates to avoid insufficient atomic diffusion enhancement due to excessively low pressure and equipment damage and lattice distortion due to excessively high pressure, resulting in more complete lattice atomic diffusion and more uniform and stable stress release; By sealing the furnace and then evacuating it, oxidation and contamination of zinc sulfide workpieces under positive pressure can be prevented. Through a combination of positive pressure protective atmosphere, full protection with graphite fiber cloth, and high-temperature rapid stress relief during annealing, the total annealing cycle is stably controlled within 120-144 hours (5-6 days). This can stably reduce the initial residual stress of zinc sulfide workpieces with an initial residual stress ≥50nm / cm to below 10nm / cm. It also prevents impurities from diffusing along the grain, thus avoiding widening and lengthening of stripe defects and their penetration into the material, ensuring the optical, mechanical, and thermal expansion properties of the crystal. Furthermore, it prevents the formation of sulfur vacancy defects, and the high-pressure airflow protection prevents surface pitting and cratering caused by the graphite fiber cloth, ensuring no surface damage and no degradation of optical and mechanical properties. The core technical indicators reach leading levels, reducing energy consumption and production costs in the annealing process. This provides core technical support for the large-scale mass production of large-size, high-performance, multispectral zinc sulfide components for high-end infrared optoelectronic equipment.
[0008] Furthermore, in step S1, the zinc sulfide workpiece is first ultrasonically cleaned with anhydrous ethanol for 10-20 minutes before being coated, then dried with argon gas, and finally placed in a dust-free environment.
[0009] The beneficial effects of adopting the above-mentioned further technical solution are as follows: ultrasonic cleaning can remove surface impurities, and after removal, it can be dried with high-purity argon gas and placed in a dust-free environment to prevent impurities from adhering to the surface of the zinc sulfide workpiece.
[0010] Furthermore, in S1, the graphite fiber is graphite fiber cloth, the graphite fiber has a carbon content ≥99.9%, an ash content ≤200ppm, a thickness of 2-3mm, and the number of coating layers is 1-3 layers.
[0011] The beneficial effects of adopting the above-mentioned further technical solution are as follows: by fully wrapping the cleaned material, the fiber cloth adheres tightly to the surface of the zinc sulfide workpiece during wrapping, without any gaps or local tension. Under positive pressure, it can uniformly adhere to the material surface, forming a flexible buffer layer and a uniform temperature layer, avoiding hard contact between the zinc sulfide workpiece and the graphite support plate, and preventing collisions between materials; it disperses the direct scouring of the positive pressure airflow, eliminates local hot spots, and ensures the uniformity of the temperature field on the material surface; and the graphite fiber cloth can be reused, avoiding damage during graphite wrapping annealing.
[0012] Furthermore, in step S1, the zinc sulfide workpiece is placed on a graphite support plate inside the furnace. The graphite support plate has a thickness of 20-50mm, and several graphite support strips are provided on both sides of the support plate.
[0013] The beneficial effects of adopting the above-mentioned further technical solutions are as follows: controlling the thickness of the graphite support plate enables it to withstand stronger pressure; the size of the graphite support plate is larger than the size of the zinc sulfide workpiece; the wrapped zinc sulfide workpiece is placed vertically in the annealing furnace with its edges facing down, which further optimizes the temperature uniformity of the zinc sulfide workpiece surface; by supporting the sides of the workpiece with several graphite support strips, various workpieces can be placed and loaded into the furnace, and a single furnace can process multiple sets of workpieces simultaneously, adapting to large-scale mass production.
[0014] Furthermore, in S2, after sealing the furnace, a vacuum is evacuated to below 2 Pa, and the pressure is maintained for 50-80 minutes before a sealing test is performed. The test shows that the pressure increase rate inside the furnace is ≤10 Pa / h. Then, argon gas is introduced into the furnace to atmospheric pressure at a flow rate of 10-30 L / min. Repeat the vacuuming and argon filling process more than 5 times to completely replace the air in the furnace.
[0015] The beneficial effects of adopting the above-mentioned further technical solution are: repeating the vacuuming and argon purging operation more than 5 times can thoroughly remove air, moisture and other oxidizing impurities in the furnace, thus avoiding high-temperature oxidation of zinc sulfide workpieces.
[0016] Furthermore, in step S3, argon gas is continuously introduced into the furnace at a flow rate of 10-30 L / min and discharged at a flow rate of 5-10 L / min, with the pressure inside the furnace reaching 150-180 kPa. When the pressure inside the furnace approaches 150-180 kPa, the argon flow rate is reduced to 5-15 L / min, and the pressure fluctuation range inside the furnace is controlled to be ≤ ±2 kPa.
[0017] The beneficial effects of adopting the above-mentioned further technical solution are as follows: After the atmosphere replacement is completed, when the pressure tends to 150-180KPa, the argon flow rate is slowed down to 5-15L / min, and the ball valve at the gas outlet of the furnace is opened to allow it to slowly exhaust gas. In the early stage, by slowly adjusting the ratio of the inlet flow rate to the outlet flow rate, the pressure fluctuation range inside the furnace is kept ≤±2KPa by PID control, while maintaining the continuous dynamic circulation of argon gas with a stable flow rate of 5-15L / min, thus ensuring the long-term stability of the purity and pressure of the atmosphere inside the furnace.
[0018] Furthermore, in step S4, when the pressure inside the furnace reaches between 150-160 kPa, a heating treatment is performed. The heating treatment is carried out at a heating rate of 90-110 °C / h to raise the temperature inside the furnace from room temperature to 480-520 °C, and the heating time is 4-6 hours. The furnace temperature is raised from 480-520℃ to 820-880℃ at a heating rate of 60-80℃ / h, and the heating time is controlled within 4-6 hours. The argon gas inlet flow rate is reduced to 5-10 L / min, and the argon gas outlet flow rate is 5-10 L / min.
[0019] The beneficial effects of adopting the above-mentioned further technical solution are as follows: The positive pressure environment of 150-160 kPa is higher than the standard atmospheric pressure. On the one hand, it can inhibit the sublimation and decomposition of zinc sulfide and avoid sulfur vacancy defects in the crystal lattice. On the other hand, it can provide additional driving force for the diffusion and migration of zinc sulfide lattice atoms, making the grain boundary migration rate more than twice that of the atmospheric pressure process. During the heating stage, the pressure inside the furnace will increase. During this period, the argon gas inlet and outlet are continuously adjusted to keep the pressure inside the furnace stable. The furnace temperature is raised from room temperature to 480-520℃ at a constant heating rate of 90-110℃ / h, and the heating time is controlled within 4-6h. This stage is adapted to the low-temperature thermal expansion characteristics of zinc sulfide and eliminates the temperature difference between the inside and outside of the workpiece. The temperature is raised to a high temperature of 820-880℃, which provides sufficient kinetic energy for atomic diffusion. Furthermore, in step S5, after heating to the first annealing temperature of 820-880℃, the furnace is kept at a constant temperature under a positive pressure atmosphere of 150-180Kpa for 20-70 hours, and the temperature of each part inside the furnace is controlled within ±3℃. The argon gas inlet flow rate is reduced to 5-10 L / min, and the argon gas outlet flow rate is 5-10 L / min.
[0020] The beneficial effects of adopting the above-mentioned further technical solution are as follows: Under the positive pressure environment of 150-180KPa, the grain boundary migration rate is increased by more than 2 times compared with the normal pressure process, which greatly shortens the heat preservation time required for stress release. After heating to the target temperature of 820-880℃, constant temperature heat preservation is carried out under the positive pressure argon atmosphere of 150-180KPa for 20-70 hours. The pressure and temperature inside the furnace are kept stable throughout the process, and the uniformity of the regional temperature field is controlled within ±3℃, ensuring that the workpiece is heated evenly and the stress is fully released.
[0021] Furthermore, in step S5, the temperature is reduced at a rate of ≤13℃ / h, and the furnace temperature is reduced from 820-880℃ to 120-130℃ in 50-70h, while maintaining a positive pressure argon atmosphere of 150-180Kpa. After the temperature drops to the second annealing temperature of 120-130℃, continue to maintain a positive pressure argon atmosphere, stop heating, and allow it to cool to room temperature. The argon gas inlet flow rate is reduced to 5-10 L / min, and the argon gas outlet flow rate is 5-10 L / min.
[0022] Furthermore, the stress of the treated zinc sulfide workpiece is ≤10nm / cm, the average infrared transmittance of the treated 8-12µm zinc sulfide workpiece is ≥70%, and the bending strength of the treated zinc sulfide workpiece is ≥70MPa.
[0023] The beneficial effects of adopting the above-mentioned further technical solution are as follows: When the temperature drops to 125℃, argon gas continues to be circulated and pressure is controlled, the heating system is shut off, the first insulation layer inside the furnace is opened, allowing the gas inside the cavity to circulate fully and the temperature to be fully released. The temperature drops rapidly to room temperature along with the furnace. The process design of uniformly cooling down to 120-130℃ in 50-70 hours avoids stress rebound caused by rapid cooling and accurately matches the critical temperature of zinc sulfide lattice diffusion. Below 125℃, lattice diffusion basically stops, and no new thermal stress is generated. There is no risk of stress rebound. While ensuring the stress relief effect, the ineffective cooling time is greatly shortened, and the total process cycle is precisely controlled to about 5 days. Attached Figure Description
[0024] 1. Workpiece; 2. Graphite support plate; 3. Graphite support strip Figure 1 This is a schematic diagram of the structure of the workpiece of the present invention in conjunction with the graphite support plate and the graphite support strip; Figure 2 This is a comparison chart of light transmittance before and after annealing treatment, measured by a visible light spectrophotometer and an infrared spectrometer according to the present invention. Figure 3 This is a diagram showing the effect of testing a large workpiece before annealing using the polarizing stress meter of this invention. Figure 4 This is a diagram showing the effect of testing a large workpiece after annealing using the polarizing stress meter of this invention. Detailed Implementation
[0025] To make the objectives, technical solutions, and advantages of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention.
[0026] like Figure 1-2As shown: This invention designs a method for stress relief in positive pressure annealing of zinc sulfide, comprising the following steps: S1: Workpiece pretreatment: The zinc sulfide workpiece is wrapped with graphite fiber and placed into a furnace; S2: Furnace gas pretreatment: The furnace is sealed and evacuated, then protective gas is introduced into the furnace and exhaust to atmospheric pressure; S3: Establishing a positive pressure atmosphere: After the furnace is at atmospheric pressure, protective gas is introduced into the furnace and exhaust to positive pressure; S4: Heating treatment: The furnace is heated, and then held at that temperature, while protective gas is introduced into the furnace and exhaust is maintained to keep the positive pressure; S5: Annealing treatment: After heating to the first annealing temperature, the temperature is held, and after holding, the temperature is lowered. Heating is stopped after the second annealing temperature is reached, and the temperature is lowered to room temperature, while protective gas is introduced into the furnace and exhaust is maintained to keep the positive pressure. By using graphite fiber encapsulation and a positive pressure temperature equalization design, temperature and stress gradients between the material's interior and surface are eliminated, allowing stress to be transferred slowly and preventing excessive deformation and surface finish changes. Establishing a positive pressure atmosphere enhances the atomic diffusion of zinc sulfide, inhibiting its sublimation and decomposition. Optimizing the holding time prevents abnormal grain growth caused by prolonged high temperatures, ensuring that the optical transmittance, uniformity, and mechanical properties of the treated multispectral zinc sulfide are not reduced. Simultaneously, at high temperatures, stress is evenly distributed throughout the interior, releasing it slowly and uniformly. The stress relief process is coordinated with parameters such as positive pressure, temperature, atmosphere, and heating / cooling rates to prevent insufficient atomic diffusion due to low pressure and equipment damage and lattice distortion due to excessive pressure, resulting in more complete atomic diffusion and more uniform and stable stress release. Finally, a vacuum is applied after sealing the furnace interior. It can prevent oxidation and impurity contamination of zinc sulfide workpieces under positive pressure. Through the synergistic annealing of positive pressure protective atmosphere, full protection with graphite fiber cloth, and high-temperature rapid stress relief, the total annealing cycle can be stably controlled within 130 hours (5 days). The initial residual stress of zinc sulfide workpieces with ≥50nm / cm can be stably reduced to below 10nm / cm. It avoids impurity diffusion along the grain, which can cause stripe defects to widen, lengthen, and penetrate into the material, thus ensuring the optical, mechanical, and thermal expansion properties of the crystal. It also avoids the generation of sulfur vacancy defects and prevents surface pitting and dents caused by high-pressure airflow under the protection of graphite fiber cloth, ensuring that the workpiece has no surface damage and no degradation of optical and mechanical properties. The core technical indicators have reached the leading level, reducing the energy consumption and production cost of the annealing process. It provides core technical support for the large-scale mass production of large-size, high-performance, multispectral zinc sulfide elements for high-end infrared optoelectronic equipment.
[0027] like Figure 2 The light transmittance before and after annealing is not significantly different. like Figure 3-4 Comparison shown Figure 4 The absence of color indicates a good annealing effect, with virtually no stress refraction after annealing. Before coating the zinc sulfide workpiece in step S1, it is first ultrasonically cleaned with anhydrous ethanol for 15 minutes, then dried with argon gas, and placed in a dust-free environment. Ultrasonic cleaning removes surface impurities, and drying with high-purity argon gas and placing it in a dust-free environment prevents impurities from adhering to the surface of the zinc sulfide workpiece.
[0028] The graphite fiber in S1 is a graphite fiber cloth with a carbon content of 99.9%, an ash content of 180 ppm, and a thickness of 2.5 mm. The coating consists of two layers. By fully wrapping the cleaned material, the fiber cloth adheres tightly to the surface of the zinc sulfide workpiece without any gaps or local tension. Under positive pressure, it can uniformly adhere to the material surface, forming a flexible buffer layer and a temperature uniformity layer. This avoids hard contact between the zinc sulfide workpiece and the graphite support plate, preventing collisions between materials. It also disperses the direct scouring of the positive pressure airflow, eliminates local hot spots, and ensures the uniformity of the temperature field on the material surface. Furthermore, the graphite fiber cloth can be reused, avoiding damage during graphite wrapping annealing.
[0029] In step S1, the zinc sulfide workpiece is placed on a graphite support plate inside the furnace. The graphite support plate is 30mm thick, and several graphite support strips are arranged on both sides of the support plate. The thickness of the graphite support plate is controlled so that it can withstand strong pressure, and the size of the graphite support plate is larger than the size of the zinc sulfide workpiece. The wrapped zinc sulfide workpiece is placed vertically in the annealing furnace with its edges facing down, which can further optimize the temperature uniformity of the zinc sulfide workpiece surface. By supporting the sides of the workpiece with several graphite support strips, various workpieces can be placed and loaded into the furnace, and a single furnace can process multiple groups of workpieces simultaneously, adapting to large-scale mass production.
[0030] In step S2, after sealing the furnace, the furnace is evacuated to below 2 Pa and held at that pressure for 70 minutes before a sealing test is performed, with the furnace pressure increase rate measured at 5 Pa / h. Then, argon gas is introduced into the furnace to atmospheric pressure at a flow rate of 21 L / min. This evacuation and argon purging process is repeated six times. This repeated evacuation and argon purging operation six times thoroughly removes air, moisture, and other oxidizing impurities from the furnace, preventing high-temperature oxidation of the zinc sulfide workpiece.
[0031] The argon gas is high-purity argon gas, with a purity ≥99.999%, an oxygen content ≤5ppm, and a water content ≤1ppm; Argon gas is continuously introduced into the furnace at a flow rate of 20 L / min in S3, and discharged at a flow rate of 7 L / min, bringing the pressure inside the furnace to 160 kPa. When the furnace pressure approaches 160 kPa, the argon flow rate is reduced to 10 L / min, controlling the furnace pressure fluctuation range to 1 kPa. After atmosphere replacement, when the pressure approaches 160 kPa, the argon flow rate is slowed down to 10 L / min, and the ball valve at the furnace outlet is opened to slowly exhaust gas. In the early stage, the furnace pressure fluctuation range is maintained within 1 kPa by slowly adjusting the ratio of inlet to outlet flow rate through PID control, while maintaining continuous dynamic circulation of argon gas with a stable flow rate of 10 L / min, ensuring long-term stability of furnace atmosphere purity and pressure.
[0032] In step S4, when the furnace pressure reaches 155 kPa, heating treatment is performed. The heating treatment raises the furnace temperature from room temperature to 500°C at a heating rate of 100°C / h for 5 hours. Then, the furnace temperature is raised from 500°C to 850°C at a heating rate of 70°C / h for 5 hours. The argon gas inlet flow rate is reduced to 7 L / min, and the argon gas outlet flow rate is 7 L / min. The positive pressure environment of 155 kPa is higher than the standard atmospheric pressure. On the one hand, it can inhibit the sublimation and decomposition of zinc sulfide and avoid sulfur vacancy defects in the crystal lattice. On the other hand, it can provide additional driving force for the diffusion and migration of zinc sulfide lattice atoms, making the grain boundary migration rate more than twice that of the atmospheric pressure process. During the heating stage, the pressure inside the furnace will increase. During this period, the argon gas inlet and outlet are continuously adjusted to keep the pressure inside the furnace stable. The furnace temperature is raised from room temperature to 500℃ at a constant heating rate of 100℃ / h, and the heating time is controlled within 5 hours. This stage is adapted to the low-temperature thermal expansion characteristics of zinc sulfide and eliminates the temperature difference between the inside and outside of the workpiece. The temperature is raised to 850℃, and the high temperature provides sufficient kinetic energy for atomic diffusion.
[0033] After heating to the first annealing temperature of 850℃ in step S5, constant temperature holding is performed under a positive pressure atmosphere of 170KPa for 50 hours, with the temperature of each part of the furnace controlled within 3℃. The argon gas inlet flow rate is reduced to 7L / min, and the argon gas outlet flow rate is 7L / min. Under the positive pressure environment of 170KPa, the grain boundary migration rate is increased by more than twice compared with the atmospheric pressure process, significantly shortening the holding time required for stress release. After heating to the target temperature of 850℃, constant temperature holding is performed under a positive pressure argon atmosphere of 170KPa for 50 hours, maintaining the stability of the pressure and temperature inside the furnace throughout the process, and controlling the temperature field uniformity of the area within 3℃ to ensure uniform heating of the workpiece and full stress release.
[0034] In step S5, the temperature is reduced at a rate of 7℃ / h, and the furnace temperature is reduced from 850℃ to 128℃ in 60h, while maintaining a positive pressure argon atmosphere of 170Kpa. After the temperature drops to the second annealing temperature of 128℃, the positive pressure argon atmosphere is maintained, heating is stopped, and the temperature is reduced to room temperature. The argon gas inlet flow rate is reduced to 7 L / min, and the argon gas outlet flow rate is 7 L / min.
[0035] The treated zinc sulfide workpiece exhibits a stress of 5 nm / cm, an average infrared transmittance of 71% for a 10 μm treated zinc sulfide workpiece, and a bending strength of 75 MPa. When the temperature drops to 128°C, argon gas is continuously supplied and pressure is controlled. The heating system is then shut off, and the first insulation layer inside the furnace is opened to allow for full gas flow and temperature release. The furnace rapidly cools to room temperature, with a 60-hour uniform cooling process to 125°C. This design avoids stress rebound caused by rapid cooling and precisely matches the critical temperature for zinc sulfide lattice diffusion. Below 125°C, lattice diffusion essentially stops, preventing the generation of new thermal stress and eliminating the risk of stress rebound. While ensuring stress relief, this significantly shortens the ineffective cooling time, precisely controlling the total process cycle to approximately 5 days.
[0036] Example 2: The content that is the same as in Example 1 will not be repeated here; the differences between this embodiment and Example 1 are as follows: This embodiment provides a method for stress relief by positive pressure annealing of zinc sulfide; in step S1, before the zinc sulfide workpiece is coated, it is first ultrasonically cleaned with anhydrous ethanol for 12 minutes, dried with argon gas, and then placed in a dust-free environment.
[0037] The graphite fiber in S1 is graphite fiber cloth, with a carbon content of 99.9%, an ash content of 170ppm, a thickness of 2.2mm, and a coating layer of 1.
[0038] In step S1, the zinc sulfide workpiece is placed on a graphite support plate inside the furnace. The graphite support plate is 25mm thick, and several graphite support strips are provided on both sides of the support plate.
[0039] In step S2, after sealing the furnace, the vacuum is evacuated to below 2 Pa, and the pressure is maintained for 55 minutes before a sealing test is performed. The pressure increase rate inside the furnace is tested to be 3 Pa / h. Then, argon gas is introduced into the furnace to atmospheric pressure at a flow rate of 12 L / min. The process of evacuating and introducing argon gas is repeated 7 times to completely replace the air in the furnace.
[0040] Argon gas is continuously introduced into the furnace at a flow rate of 15 L / min in S3, and discharged at a flow rate of 6 L / min, bringing the pressure inside the furnace to 160 kPa. When the pressure inside the furnace approaches 155 kPa, the argon flow rate is reduced to 6 L / min to control the pressure fluctuation range inside the furnace to -1 kPa.
[0041] In step S4, when the pressure inside the furnace reaches 152 kPa, a heating treatment is performed. The heating treatment raises the temperature inside the furnace from room temperature to 490°C at a heating rate of 95°C / h, and the heating time is 4.2h. The furnace temperature was raised from 490℃ to 830℃ at a heating rate of 65℃ / h, with the heating time controlled at 4.2h.
[0042] The argon gas inlet flow rate is reduced to 6 L / min, and the argon gas outlet flow rate is 6 L / min.
[0043] In step S5, after heating to the first annealing temperature of 830°C, constant temperature holding is performed under a positive pressure atmosphere of 160 kPa for 30 hours, and the temperature of each part of the furnace is controlled within -2°C. The argon gas inlet flow rate is reduced to 6 L / min, and the argon gas outlet flow rate is 6 L / min.
[0044] In S5, the temperature is reduced at a rate of ≤13℃ / h, and the furnace temperature is reduced from 830℃ to 122℃ in 55h, while maintaining a positive pressure argon atmosphere of 160Kpa. After the temperature drops to the second annealing temperature of 122°C, continue to maintain a positive pressure argon atmosphere, stop heating, and allow it to cool to room temperature. The argon gas inlet flow rate is reduced to 6 L / min, and the argon gas outlet flow rate is 6 L / min.
[0045] The treated zinc sulfide workpiece has a stress of 3 nm / cm, an average infrared transmittance of 71% for the 8 μm treated zinc sulfide workpiece, and a bending strength of 72 MPa.
[0046] Example 3: The content that is the same as in Example 2 will not be repeated here; the differences between this embodiment and Example 2 are as follows: This embodiment provides a method for stress relief by positive pressure annealing of zinc sulfide; in step S1, before the zinc sulfide workpiece is coated, it is first ultrasonically cleaned with anhydrous ethanol for 18 minutes, dried with argon gas, and then placed in a dust-free environment.
[0047] The graphite fiber in S1 is graphite fiber cloth, with a carbon content of 100%, an ash content of 190ppm, a thickness of 2.8mm, and a coating layer of 3 layers.
[0048] In step S1, the zinc sulfide workpiece is placed on a graphite support plate inside the furnace. The graphite support plate is 40mm thick, and several graphite support strips are provided on both sides of the support plate.
[0049] In step S2, after sealing the furnace, the vacuum is evacuated to below 2 Pa, and the pressure is maintained for 75 minutes before a sealing test is performed. The pressure increase rate inside the furnace is tested to be 8 Pa / h. Then, argon gas is introduced into the furnace to atmospheric pressure at a flow rate of 27 L / min. The process of evacuating and introducing argon gas is repeated 8 times to completely replace the air in the furnace.
[0050] Argon gas is continuously introduced into the furnace at a flow rate of 25 L / min in S3, and discharged at a flow rate of 8 L / min, bringing the pressure inside the furnace to 170 kPa. When the pressure inside the furnace approaches 170 kPa, the argon flow rate is reduced to 13 L / min to control the pressure fluctuation range inside the furnace within 1 kPa.
[0051] In step S4, when the pressure inside the furnace reaches 158 kPa, a heating treatment is performed. The heating treatment raises the temperature inside the furnace from room temperature to 510°C at a heating rate of 105°C / h, and the heating time is 5.5h. The furnace temperature was raised from 510℃ to 870℃ at a heating rate of 70℃ / h, with the heating time controlled at 5.5h.
[0052] The argon gas inlet flow rate is reduced to 9 L / min, and the argon gas outlet flow rate is 9 L / min.
[0053] In step S5, after heating to the first annealing temperature of 870°C, constant temperature holding is performed under a positive pressure atmosphere of 170 kPa for 65 hours, and the temperature of each part of the furnace is controlled within 2°C. The argon gas inlet flow rate is reduced to 8 L / min, and the argon gas outlet flow rate is 8 L / min.
[0054] In step S5, the temperature is reduced at a rate of ≤13℃ / h, and the furnace temperature is reduced from 870℃ to 125℃ in 65h, while maintaining a positive pressure argon atmosphere of 170Kpa. After the temperature drops to the second annealing temperature of 125°C, continue to maintain a positive pressure argon atmosphere, stop heating, and allow it to cool to room temperature. The argon gas inlet flow rate is reduced to 8 L / min, and the argon gas outlet flow rate is 8 L / min.
[0055] The treated zinc sulfide workpiece has a stress of 9 nm / cm, an average infrared transmittance of 70% for the 12 μm treated zinc sulfide workpiece, and a bending strength of 77 MPa.
[0056] The above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit it. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for stress relief through positive pressure annealing of zinc sulfide, characterized in that: S1: Workpiece pretreatment: The zinc sulfide workpiece is wrapped with graphite fiber and then placed into the furnace. S2: Pretreatment of gas inside the furnace: After sealing the furnace, vacuum the furnace, then fill the furnace with protective gas and exhaust the gas to atmospheric pressure. S3: Establish positive pressure atmosphere: After the furnace is at normal pressure, continue to fill the furnace with protective gas and exhaust it to positive pressure; S4: Heat treatment: Heat the furnace inside the furnace. During the heat treatment, keep the furnace filled with protective gas and exhaust gas to maintain positive pressure. S5: Annealing treatment: After heating to the first annealing temperature, hold the temperature, then cool down. After reaching the second annealing temperature, stop heating and let it cool to room temperature. During the annealing treatment, keep the furnace filled with protective gas and exhaust gas to maintain positive pressure.
2. The method for stress relief by positive pressure annealing of zinc sulfide according to claim 1, characterized in that: Before coating the zinc sulfide workpiece in S1, it is first ultrasonically cleaned with anhydrous ethanol for 10-20 minutes and then dried with argon gas.
3. The method for stress relief by positive pressure annealing of zinc sulfide according to claim 1, characterized in that: The graphite fiber in S1 is graphite fiber cloth with a carbon content ≥99.9%, ash content ≤200ppm, and thickness of 2-3mm. The number of coating layers is 1-3.
4. The method for stress relief by positive pressure annealing of zinc sulfide according to claim 1, characterized in that: In step S1, the zinc sulfide workpiece is placed on a graphite support plate inside the furnace. The thickness of the graphite support plate is 20-50mm, and several graphite support strips are provided on both sides of the support plate.
5. The method for stress relief by positive pressure annealing of zinc sulfide according to claim 1, characterized in that: In step S2, after sealing the furnace, the vacuum is evacuated to below 2 Pa, and the pressure is maintained for 50-80 minutes before a sealing test is performed. The test shows that the pressure increase rate inside the furnace is ≤10 Pa / h. Then, argon gas is introduced into the furnace to atmospheric pressure at a flow rate of 10-30 L / min. Repeat the vacuuming and argon filling process more than 5 times to completely replace the air in the furnace.
6. The method for stress relief by positive pressure annealing of zinc sulfide according to claim 1, characterized in that: Argon gas is continuously introduced into the furnace at a flow rate of 10-30 L / min in S3, and discharged at a flow rate of 5-10 L / min, with the pressure inside the furnace reaching 150-180 kPa. When the pressure inside the furnace approaches 150-180 kPa, the argon gas flow rate is reduced to 5-15 L / min, and the pressure fluctuation range inside the furnace is controlled to be ≤±2 kPa.
7. The method for stress relief by positive pressure annealing of zinc sulfide according to claim 1, characterized in that: In step S4, when the pressure inside the furnace reaches between 150-160 kPa, a heating treatment is performed. The heating treatment is carried out at a heating rate of 90-110℃ / h, raising the temperature inside the furnace from room temperature to 480-520℃, and the heating time is 4-6h. The furnace temperature is raised from 480-520℃ to 820-880℃ at a heating rate of 60-80℃ / h, and the heating time is controlled within 4-6 hours. The argon gas inlet flow rate is reduced to 5-10 L / min, and the argon gas outlet flow rate is 5-10 L / min.
8. The method for stress relief by positive pressure annealing of zinc sulfide according to claim 1, characterized in that: In step S5, after heating to the first annealing temperature of 820-880℃, constant temperature holding annealing is carried out under a positive pressure atmosphere of 150-180Kpa for 20-70h, and the temperature of each part of the furnace is controlled within ±3℃. The argon gas inlet flow rate is reduced to 5-10 L / min, and the argon gas outlet flow rate is 5-10 L / min.
9. The method for stress relief by positive pressure annealing of zinc sulfide according to claim 1, characterized in that: In S5, the temperature is reduced at a rate of ≤13℃ / h, and the furnace temperature is reduced from 820-880℃ to 120-130℃ in 50-70h, while maintaining a positive pressure argon atmosphere of 150-180Kpa. After the temperature drops to the second annealing temperature of 120-130℃, continue to maintain a positive pressure argon atmosphere, stop heating, and allow it to cool to room temperature. The argon gas inlet flow rate is reduced to 5-10 L / min, and the argon gas outlet flow rate is 5-10 L / min.
10. The method for stress relief by positive pressure annealing of zinc sulfide according to claim 1, characterized in that: The stress of the treated zinc sulfide workpiece is ≤10nm / cm, the average infrared transmittance of the treated 8-12µm zinc sulfide workpiece is ≥70%, and the bending strength of the treated zinc sulfide workpiece is ≥70MPa.